TiO₂-2 radiating damages as a result of the irradiation helium ions with energies of 0.12 and 4 MeV on the linear accelerator - Butenko, V.I.; Cenian, A.; Dyachenko, O.F.; Manuilenko, O.V.; Pavlii, K.V.; Sawczak, M.; Zajtsev, B.V.; Zhurba, V.I. (Problems of Atomic Science and Technology, 2023)
On the linear accelerator of helium ions, the irradiation of TiO₂-2 samples with ions energy of 0.12 and 4 MeV to doses of ≈ 1∙10¹⁸ ion/cm² is executed. The elemental composition of TiO₂-2 samples is made by roentgen-fluorescence method. After irradiation a change of electrophysical characteristics is investigated, microscopic researches on electronic and optical microscopes are conducted. Numerical calculations of atom sputtering ratios taking into account of input angles of helium ions in a sample, and also phonons formation, atoms redistribution (segregation), appearance of the vacancies and displacements in TiO₂-2 sample are made. Processes of the flaking formation are investigated, and also presence of the metallization effect and long-range interaction effect in the irradiated samples is shown. На лінійному прискорювачі іонів гелію виконано опромінення зразків TiO₂-2 з енергією іонів 0,12 і 4 МеВ до доз ≈ 1∙10¹⁸ іон/см². Елементний склад зразків TiO₂-2 отримано рентгенофлюоресцентним методом. Після опромінення проведено мікроскопічні дослідження на електронному та оптичному мікроскопах, досліджено змінення електрофізичних характеристик. Зроблено числові розрахунки коефіцієнтів розпилення атомів з урахуванням кутів входу іонів гелію в зразок, а також утворення фононів, перерозподілу атомів (сегрегація), утворення вакансій і зміщень у зразкa TiO₂-2. Досліджено процеси утворення флекінгу та показано наявність ефектів металізації й далекодії в опромінених зразках.